2003
DOI: 10.1001/jama.289.20.2685
|View full text |Cite
|
Sign up to set email alerts
|

Combined Cardiac Resynchronization and Implantable Cardioversion Defibrillation in Advanced Chronic Heart Failure

Abstract: N IMPORTANT SUBSET OF PAtients who have chronic heart failure (HF) also have cardiac dyssynchrony. Delays in interventricular or intraventricular electrical activation cause marked abnormalities in the sequence of global and segmental right and left ventricular (LV) activation and impair mechanical performance. 1-3 The ability of new methods of cardiac stimulation to resynchronize ventricular function, improve overall cardiac performance, and increase exercise capacity has been shown by the results of several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
223
1
11

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,437 publications
(243 citation statements)
references
References 28 publications
8
223
1
11
Order By: Relevance
“…In these 2 studies, significant reverse remodeling and improvement in LVEF were seen in NYHA class III and IV patients receiving CRT. 1,2,13 In the present study, CRT produced significant improvement in LV systolic and diastolic volumes and LVEF, indicating that CRT promotes reverse remodeling even in patients with less symptomatic heart failure. These effects did not translate into improved exercise capacity, however.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In these 2 studies, significant reverse remodeling and improvement in LVEF were seen in NYHA class III and IV patients receiving CRT. 1,2,13 In the present study, CRT produced significant improvement in LV systolic and diastolic volumes and LVEF, indicating that CRT promotes reverse remodeling even in patients with less symptomatic heart failure. These effects did not translate into improved exercise capacity, however.…”
Section: Discussionsupporting
confidence: 54%
“…The sites, investigators, and coordinators participating in the MIRACLE ICD II trial are identical to those contributing to the MIRACLE ICD study and are listed elsewhere. 2 …”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Data regarding the effects of CRT on arrhythmia occurrence are sparse. The Multicenter InSync ICD Randomized Clinical Evaluation (MIRACLE-ICD) trial 4 showed no significant difference in ventricular arrhythmia frequency or appropriate implantable cardioverter-defibrillator (ICD) therapies between patients receiving biventricular pacing and controls. However, more recent data suggest that CRT may decrease the frequency of ventricular arrhythmias, possibly through reverse remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…In den letzten Jahren haben eine Reihe von Studien die technische Durchführbarkeit der biventrikulären Stimulation und deren therapeutischen Effekt auf die Leistungsfähigkeit bei herzinsuffizienten Patienten nachgewiesen [6,7]. Mit COMPANION und CARE-HF liegen nun zwei Studien vor, welche auch eine Mortalitätsreduktion durch CRT demonstrieren konnten [1,8].…”
Section: Mortalitätsstudien Zur Kardialen Resynchronisationstherapieunclassified